"Many Lands Have I Left Behind Me": E. A. Baratynskii’s Quest for Happiness in Finland, Italy, and the Homeland - Clark, Elena Pedigo (Poljarnyj vestnik, 2014)
This article examines the poetry of E.A. Baratynskii about three specific places: Finland, the homeland (i.e. Russia), and Italy. It is the contention of this article that these place-specific poems form a contrast to Baratynskii's other poetry, and allow his poetic persona to resolve conflicts that remain unresolved in the majority of his oeuvre. In particular, this article discusses the ways in which these three places form three different "realms of the dead" or areas of contact with the divine or the supernatural, thus allowing the poet to transcend the binary conflict between intellect and feeling, and science and nature, that is so problematic for his poetic persona.